2007
DOI: 10.1111/j.1462-5822.2006.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin is required for F-actin assembly and pedestal formation by enteropathogenic Escherichia coli (EPEC)

Abstract: SummaryAfter attaching to human intestinal epithelial cells, enteropathogenic Escherichia coli (EPEC) induces the formation of an actin-rich pedestal-like structure. The signalling pathway leading to pedestal formation is initiated by the bacterial protein Tir, which is inserted into the host cell plasma membrane. The domain exposed on the cell surface binds to another bacterial protein, intimin, while one of the cytoplasmic domains binds the adaptor protein Nck. This leads to recruitment of other cytoskeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…For instance, internalized occludin colocalizes with caveolin-1 and dynamin II, which is blocked by dominant negative dynamin II (K44A) and inhibition of caveola-mediated endocytosis by cholesterol extraction prevented both latrunculin A-induced TER loss and occludin internalization (41). Conversely, for EPEC infections, other authors have found that dynamin is required for F-actin assembly and pedestal formation by EPEC E2348/69 (47) and that EPEC E2348/69 Tir translocation and pedestal formation require membrane cholesterol (1). Recently, Alto et al (2) also reported that that the type III effector EspF coordinates membrane remodeling and F-actin polymerization during EPEC pathogenesis, since EspF activated both SNX9 and N-WASP in a coordinated spatiotemporal pattern at clathrin-coated pits, again indicating a relationship between endocytosis and actin polymerization.…”
Section: Infect Immunmentioning
confidence: 99%
“…For instance, internalized occludin colocalizes with caveolin-1 and dynamin II, which is blocked by dominant negative dynamin II (K44A) and inhibition of caveola-mediated endocytosis by cholesterol extraction prevented both latrunculin A-induced TER loss and occludin internalization (41). Conversely, for EPEC infections, other authors have found that dynamin is required for F-actin assembly and pedestal formation by EPEC E2348/69 (47) and that EPEC E2348/69 Tir translocation and pedestal formation require membrane cholesterol (1). Recently, Alto et al (2) also reported that that the type III effector EspF coordinates membrane remodeling and F-actin polymerization during EPEC pathogenesis, since EspF activated both SNX9 and N-WASP in a coordinated spatiotemporal pattern at clathrin-coated pits, again indicating a relationship between endocytosis and actin polymerization.…”
Section: Infect Immunmentioning
confidence: 99%
“…We attempted to assess this but were unable to accurately localize dynamin at pedestals. This was likely due to the different antibodies that were used by Unsworth and coworkers (18) and those that we could acquire commercially. How does clathrin and the endocytic machinery mediate pedestal formation and not bacterial internalization?…”
Section: Discussionmentioning
confidence: 92%
“…Dynamin-2 was also recently identified at EPEC pedestals (18). During endocytosis, dynamin-2 has a dual function in both formation of the endocytic vesicle and pinching off from the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations